Omics of Climate Resilient Small Millets - Pudake, Ramesh Namdeo; Solanke, Amolkumar U.; Sevanthi, Amitha Mithra; Rajendrakumar, P. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This edited book covers all aspects of omics approaches used for the varietal improvement of millets in changing climatic conditions. Millets are the collection of small-grained cereal grasses, that are grown for human carbohydrate needs. They are among the oldest crops, mainly divided into two groups - Major and small millets based on seed size. Small millets are earlier considered orphan crops, but recently due to their nutritional values, they are getting importance in cultivation. This book explores the genomics, transcriptomics, proteomics, metabolomics, bioinformatics, and other omics tools that are being widely used to get a clear understanding of mechanistic approaches taken by plant genes to tolerate stress. Various reports are published based on field breeding on these crops, and recently the genome of some of the small millets is released, and many omics studies are published related to its application in varietal improvements. This book reviewed all those recent studies and is of interest to research students, plant breeding scientists, teachers that are working in agriculture and plant biotech universities. Along with this, the book serves as reference material for undergraduate and graduate students of agriculture, and biotechnology. National and international agricultural scientists, policymakers will also find this to be a useful read.
Small Millets - the Next-Generation Smart Crops in the Modern Era of Climate Change -- Omics for abiotic stress tolerance in foxtail millet -- Current status and future prospects of omics strategies in barnyard millet -- Role of inducible promoters and transcription factors in conferring abiotic stress-tolerance in small millets -- Genome-wide identification and expression profiling of non-coding RNAs in response to abiotic stresses in small millets -- Insights into abiotic stress tolerance in small millets through transcriptomics -- Role of proteomics in understanding the abiotic stress tolerance in minor millets -- Plant regeneration and transgenic approaches for the development of abiotic stress tolerant small millets -- Mining genes and markers across minor millets using comparative genomics approaches -- Improving the nutrient-use efficiency in millets by genomics approaches -- Current status of bioinformatics resources of small millets -- Advances in omics for enhancing abiotic stress tolerance in finger millets -- Genome editing approaches for abiotic stress tolerance in small millets -- Integrating genomics and phenomics tools to dissect climate resilience traits in small millets -- Abiotic stress tolerant small millet plant growth regulation by long noncoding RNAs: an omics perspective -- Omics of climate change on nutritional quality of small millets -- Exploring genome wide analysis of heat shock proteins (HSPs) in small millets as potential candidates for development of multistress tolerant crop plants.
Keywords: Agriculture; Genetics; Plant physiology; Stress (Physiology).; Plants; Agriculture; Genetics and Genomics; Plant Physiology; Plant Stress Responses